EFFICACY OF MICRONEEDLING VERSUS FRACTIONAL CO2 LASER IN TREATMENT OF ATROPHIC FACIAL ACNE SCAR: A RANDOMIZE CONTROL TRAIL - Mehak Mukhtar; Arfa Ikram; Javeria Javed; Amina Rahat; Assad Ullah (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Post-acne scarring is very distressing for the patient and difficult for dermatologists to treat. Many treatments are available for treating post acne scars but optimized treatment does not still exist. Microneedling and CO2 laser are both promising modalities in treatment of post acne scarring and have both resulted in clinical improvement. Objectives: The main objective of the study is to evaluate the efficacy of fractional CO2 laser in comparison with micro needling fractional radiofrequency in the management of post acne scars. Material and methods: It was a randomized controlled trial conducted in dermatology unit of Lady Reading Hospital, Peshawer from 12th of October 2020 to 10th March, 2021. Total of 188 patients enrolled in the study, all suffering from atrophic facial acne scars having an age range between 16-40 years. The 188 patients were randomly divided into two groups by lottery method, each involved 94 patients; group A received micro needling radiofrequency, and group B included patients who were offered fractional CO2 laser. Both groups statistically matched regarding age, gender, severity of acne scars. Efficacy was evaluated after 5 months of treatment and determined in terms of the percentage of number of lesions cleared from baseline. A clearance of more than 50% of lesions from baseline would be considered effective at 5th month follow up. Results: Results exposed that, both group of patients displayed statistically significant percentage of improvement (p < 0.05). As per calculated sample size, a total of 188 patients i.e. 94 patients in each group were divided into two groups, A and B. Group with fractional CO2 laser treatment showed 88.3% efficacy i.e. 83 patients showed improvement while those receiving microneedling therapy were 84% effective i.e. 79 patients showed more than 50% improvement in lesions from base line. Conclusion: It is concluded that, our study highlights that the treatment of atrophic facial acne scars fractional CO2 laser is more effective then micro needling radiofrequency sessions.